Pengaruh Pemenuhan Slot Time Terhadap Target Take-Off Time di Perum LPPNPI Cabang Utama Jakarta Air Traffic Service Center - Zonar Anjab Rabbani; Togi Adnan M.S; Yudha Abimanyu (Politeknik Penerbangan Indonesia Curug, 2021)
This research was conducted at the Jakarta Air Traffic Service Center (JATSC) starting from March 2020 to July 2020 using the quantitative associative correlation method. The research population was all departing aircraft at Soekarno-Hatta International Airport using various runways and taxiways and aprons. The samples used were all aircraft departing from Soekarno-Hatta International Airport and navigation services were provided by the Jakarta Air Traffic Service Center (JATSC) in three, namely from November 2019 to January 2020 and using cluster (area) sampling techniques. The data collection technique used is a documentation study containing data on the fulfillment of Target Take Off Time (TTOT) and data on each aircraft movement required for research (such as aircraft identification, Estimate Off Block Time, taxi time, etc.). Furthermore, the data analysis technique used is parametric statistics in the form of data assumption tests followed by relationship analysis tests.